2007
DOI: 10.1007/s11738-007-0049-y
|View full text |Cite
|
Sign up to set email alerts
|

Organospecific responses of lupin seedlings to lead Localization of hydrogen peroxide and peroxidase activity

Abstract: In an earlier work using tissue printing method, we found that the PR-10 stress protein was observed in leaf petiole of lupin seedling where lead was not detected (Przymusiński et al. 2001). These results suggested the presence of substance(s) mediating a signal transduction from directly affected cells to distant organs. As the hydrogen peroxide was found to be involved in signal transduction pathway, in the present paper, we analysed the level of H 2 O 2 in the organ of lupin seedlings exposed to Pb 2+ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…H 2 O 2 is an example of ROS whose content increased in the presence of lead ions. A similar effect was found in many species of land plants, including Allium sativum [ 132 ], Brassica campestris [ 125 ], Lupinus luteus [ 133 ], Pisum sativum [ 102 ], Sedum alfredii [ 134 ], Talinum triangulare [ 135 ], Triticum aestivum [ 136 ], and Vicia faba [ 137 ]. There is little information about aquatic plants in this context.…”
Section: Discussionsupporting
confidence: 54%
“…H 2 O 2 is an example of ROS whose content increased in the presence of lead ions. A similar effect was found in many species of land plants, including Allium sativum [ 132 ], Brassica campestris [ 125 ], Lupinus luteus [ 133 ], Pisum sativum [ 102 ], Sedum alfredii [ 134 ], Talinum triangulare [ 135 ], Triticum aestivum [ 136 ], and Vicia faba [ 137 ]. There is little information about aquatic plants in this context.…”
Section: Discussionsupporting
confidence: 54%
“…The excess of TMs in plant cells can cause a range of toxic alterations, e.g., the generation of reactive oxygen species (ROS) resulting in oxidative stress (Rucińska-Sobkowiak and Pukacki 2006;Przymusiński et al 2007), which leads to the destruction of cell membranes: the PM, the endomembrane system and membranous organelles, in particular chloroplast, mitochondrion (Hall 2002;Patra et al 2004) and nucleus (Prasad 2004;Glińska et al 2007). Furthermore, trace metals, especially non-essential ones, can destroy enzyme functioning by entering in place of proper ions for building their molecules or by binding to their sulfhydryl and carboxyl groups, thereby changing their conformation (Hall 2002;Patra et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This result complements the previous studies carried out on lupine roots, where an increased level of free radicals (Rucińska et al 1999) and superoxide dismutase activity (Przymusiński et al 1995) was demonstrated in lead treated lupine seedlings. It has been proved that H 2 O 2 induces gene expression of PR-proteins and their accumulation under lead treatment (Przymusiński et al 2001(Przymusiński et al , 2007.…”
Section: Resultsmentioning
confidence: 99%